Blood, Blood Everywhere and Not A Drop To Drink: How Jesus’ Blood Fulfills the Law - Moon, Catherine (Lumen et Vita, 2017)
Christianity is based in blood, thereby that death can never be forgotten. Blood begins with Genesis to have the dueling significance of life and death. For one’s blood is one’s life, and yet blood is the price for sin. From the very beginning blood poured out represents humanity’s imminent death brought even closer by the onslaught of sin and its weariless pursuit of life. Until Christ fulfills his new covenant, the exchange of blood for blood is endless and the death that permeates blood prevails over life. In this essay, I will analyze how Jesus’ blood fulfills the Law and frees humanity from sin and death. First, I will see how blood is understood and portrayed in the covenant of Noah, then the covenant of Abraham, and finally in the Law of Moses, so that the fullness of what it means for God to pour out His blood and die, so humanity may ultimately live and not be forever separated from Him can be fully known. This will also further unpack and clarify what the practice of communion and activity of the mass effects in human beings according to piece of human history it fulfills, forever partakes, and from which it came into being.